Statistical analysis for the soccer matches of the First Bundesliga - Yue, Z.; Broich, H.; Mester, J. (International Journal of Sports Science and Coaching, 2014)
Statistical analysis for the soccer matches of the First Bundesliga; i.e., the first national soccer league of Germany, during the period Aug. 5 to Nov. 27, 2011 is made in order to see which parameters are more important for the result of a match. It is found that the goal efficiency, defined by the number of goals divided by the number of shots, is by far the most important parameter. The parameters of the second to the fourth importance are the number of shots, the number of passes and the number of ball contacts respectively. The present analysis shows that the quality of shots, represented by the goal efficiency, is more important than the quantity of shots for winning a soccer game. Regarding the long time dispute over the issue whether "direct play" or "possession play" is more effective, the present result favours "direct play" because it has higher goal efficiency compared to "possession play" according to the literature. Nevertheless, the length of passing sequence may not be the major factor related to the goal efficiency. Effective use of team possessions to create favourable shooting conditions may be more important for raising the goal efficiency. Much further analysis remains to be carried out in this direction.